Вплив стереотипів на зовнішнє сприйняття - Аджабі, Яссін; Adjabi Ya. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглядаються значення стереотипів, різні типи стереотипів та їхній вплив на міжкультурне сприйняття та комунікацію між представниками різних культур. Також наведено семантичну інтерпретація стереотипів для виключення неправильного контекстуального та семантичного розуміння, що призводить до різного роду непорозумінь. У динаміці міжособистісних та міжгрупових відносин стереотипи вживаються для забезпечення впевненості, подолання збентеження, соціального порівняння, підкреслення ідентичності, самовираження та стереотипізації. Стереотипи сприяють зближенню культур та суспільств, допомагають зрозуміти національний спосіб мислення та сприйняття, як «трансккультурна зброя» безперечно можуть змінити національний менталитет, що доводить необхідність їхнього дослідження. The following article is focused on the considerable necessity of stereotypes and their influences on the foreign perception and on the communication between peoples from different cultures. It deals too with the different types of stereotypes and their semantic interpretation in special contexts because those wrong contextual and semantic interpretation of stereotypes while intercultural interaction leads us to misunderstandings and then some ideas will be anchored in our minds without having any real presentation about what the other means or try to inform. In order to have some dynamic relations between different groups, stereotypes are used to facilitate the confidence, perception, social equality, reinforcement of identity and self-expression. These stereotypes are like cultural prejudices breaking all kind of foreign perception and the intercultural interactions. Besides stereotypes permit to understand culture and society, to understand the national thought and perception; they are like a “trans-cultural weapon” helping to change the national mentality. They need to be searched more and more in different disciplines.
The Influence of Stereotypes on the Foreign Perception
Keywords: стереотипи; stereotypes; комунікація; communication; міжкультурна комунікація intercultural; communication